Nanosecond Time-Resolved Resonance Raman Spectroscopy - Varotsis, Constantinos; Babcock, Gerald T. (My University, 1993)
Resonance Raman (RR) spectroscopy is a powerful technique to probe molecular vibrations that are coupled to electronic transitions. Monochromatic light, now universally obtained from continuous wave (CW) or pulsed lasers, is used to illuminate a sample, and the spectrum of scattered radiation is analyzed to determine vibrational information on molecular species within the sample. By bringing the laser frequency into resonance with an electronic transition of a species of interest, dramatic enhancements in scattered intensity result. The individual vibrational frequencies observed in a Raman spectrum arise from normal modes in the ground electronic state. The intensities of the Raman lines, however, reflect the character of the electronic excited states. Owing to the high selectivity and sensitivity in the enhancement of vibrational modes, resonance Raman spectroscopy offers the opportunity to probe chemical species such as reaction intermediates, excited electronic states, and chromophoric site(s) of biological systems. Biological chromophores such as heroes, flavins, chlorophylls, and a number of different types of metal-containing proteins are investigated by resonance Raman spectroscopy. The static resonance Raman effect and biological applications of Raman spectroscopy has been the subject of numerous reports and reviews. Time-resolved resonance Raman (TR3) spectroscopy is a technique that can be used to probe structural and conformational as well as kinetic properties of transient species. The two-pulse, pump-probe, time-resolved Raman approach, in conjunction with a single monochromator and a CCD detector, provides the most reliable configuration to record the time evolution of transient species.
Keywords: Cytochrome c oxidase; Hemoglobin; Metalloprotein; Myoglobin